HIF-α Prolyl Hydroxylase Inhibitors and Their Implications for Biomedicine: A Comprehensive Review - Kiichi Hirota (Biomedicines, 2021)
Oxygen is essential for the maintenance of the body. Living organisms have evolved systems to secure an oxygen environment to be proper. Hypoxia-inducible factor (HIF) plays an essential role in this process; it is a transcription factor that mediates erythropoietin (EPO) induction at the transcriptional level under hypoxic environment. After successful cDNA cloning in 1995, a line of studies were conducted for elucidating the molecular mechanism of HIF activation in response to hypoxia. In 2001, cDNA cloning of dioxygenases acting on prolines and asparagine residues, which play essential roles in this process, was reported. HIF-prolyl hydroxylases (PHs) are molecules that constitute the core molecular mechanism of detecting a decrease in the partial pressure of oxygen, or hypoxia, in the cells; they can be called oxygen sensors. In this review, I discuss the process of molecular cloning of HIF and HIF-PH, which explains hypoxia-induced EPO expression; the development of HIF-PH inhibitors that artificially or exogenously activate HIF by inhibiting HIF-PH; and the significance and implications of medical intervention using HIF-PH inhibitors.